The Impact of Digital Transformation on Career Growth: Mediating Role of Job Satisfaction and Moderating Effect of Organizational Support in the Manufacturing Sector - Bawazir, Abdullah Abdulaziz; Mahbob, Nur Nadiah; Hasim, Muhammad Asyraf (International Review of Management and Marketing, 2025)
This study investigates the relationship between digital transformation and career growth in a manufacturing company in Johor, Malaysia. A total of 283 employees participated in this study. The study uses SmartPLS to examine the direct effects of digital transformation, digital skills, and technology adoption on career growth. Additionally, it explores the moderating role of organisational support and the mediating role of job satisfaction in these relationships. The findings reveal that digital transformation significantly enhances career growth by fostering skills development, improving job performance, and increasing job satisfaction. Employees with high digital proficiency reported more significant career advancement, particularly when organisational support and job satisfaction were present. Job satisfaction was found to mediate the relationships between digital transformation, digital skills, technology adoption, and career growth, highlighting its importance in fostering career progression. Organisational support further strengthened the positive effects of these factors on career growth. This research provides valuable insights for organisations that leverage digital transformation to enhance employee career development and overall satisfaction. Recommendations for future research and practical applications are also discussed.